Social Structure, Social Stratification, and Social Conflict in Society: A Literature Review and Implication for Guidance and Counseling - Soeci Izzati Adlya; Neviyarni S (Universitas Negeri Padang, 2025)
Social structure, social stratification, and social conflict are fundamental elements in understanding the dynamics of community life and their impact on individual welfare. This article aims to comprehensively examine the concepts of social structure, social stratification, and social conflict, as well as analyze their implications for guidance and counseling practices. The method used is a literature review by examining various relevant scientific sources, both books and reputable journal articles, to obtain a deep conceptual and empirical understanding. The results of the study show that social structure is formed through the interrelationship of status, roles, groups, institutions, norms, and values that regulate patterns of interaction in society. Social stratification creates hierarchical layers that have implications for unequal access to resources, opportunities, and social services. These conditions have the potential to trigger social conflicts arising from individual, cultural, political and economic differences, as well as social changes accelerated by globalization and digital technology. In the context of guidance and counseling, understanding the reality of social structure and stratification is crucial for counselors to be able to provide fair, inclusive, and non-discriminatory services. Therefore, counselors are required to have multicultural competence and conflict management skills to support the optimal development of clients in a diverse and dynamic society